Leaf Epidermal Properties of Two Bougainvillea spectabilis Willd. Cultivars (Red Bract and White Bract) Cultivated in Sana’a University New Campus - Aqlan, Esam M.; Khaled, Juhaina; Al-muhares, Mariam M.; Ibrahim, Hassan M. (PSM Biological Research, 2025)
This study investigated the taxonomic significance of 24 leaf epidermal characters, in two cultivars of Bougainvillea spectabilis: red bract and white bract cultivars. Our analysis revealed eight quantitative properties that significantly differentiated between the two cultivars. These included five quantitative properties observed on both the adaxial and abaxial surfaces: the number of epidermal cells per 400x field of view, the number of trichomes per 400x view, the trichome index, the number of stomata per 400x view, and the percentage of Tetracytic stomata. Additionally, three quantitative properties specific to the adaxial surface were determined: epidermal cell width, stomatal index, and percentage of Polycytic stomata (five subsidiary cells). To further assess the taxonomic relationship between cultivars, two-way cluster analysis (TWCA) was employed on the 24 leaf epidermal characters, resulting in a dendrogram that segregated the two cultivars at a high similarity level of 93.85%. These findings indicated that the two cultivars represent distinct taxa within the same species.